2016
DOI: 10.2166/wqrjc.2016.020
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of old landfill leachate and municipal wastewater in sequencing batch reactor (SBR): effect of landfill leachate concentration

Abstract: Sequencing batch reactor (SBR) was assessed for direct co-treatment of old landfill leachate and municipal wastewater for chemical oxygen demand (COD), nutrients and turbidity removal. Nitrogen removal was achieved by sequential nitrification and denitrification under post-anoxic conditions. Initially, SBR operating conditions were optimized by varying hydraulic retention time (HRT) at 20% (v/v) landfill leachate concentration, and results showed that 6 d HRT was suitable for co-treatment. SBR performance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Anaerobic systems offer advantages such as: high organic loading rates capacity; methane production; low sludge generation and the capability of retaining microbes with special functions (Miao et al, 2016). Several studies proved the biological treatment processes based on suspended-growth biomass, exhibit satisfactory and consistent performance in terms of organic carbon and nutrients removal due to their simplicity and cost-effectiveness (Aziz et al, 2012;Contrera et al, 2014;Luo et al, 2020;Mojiri et al, 2014;Ranjan et al, 2016;Yin et al, 2018). Thus, providing enough hydraulic residence time.…”
Section:  Biological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic systems offer advantages such as: high organic loading rates capacity; methane production; low sludge generation and the capability of retaining microbes with special functions (Miao et al, 2016). Several studies proved the biological treatment processes based on suspended-growth biomass, exhibit satisfactory and consistent performance in terms of organic carbon and nutrients removal due to their simplicity and cost-effectiveness (Aziz et al, 2012;Contrera et al, 2014;Luo et al, 2020;Mojiri et al, 2014;Ranjan et al, 2016;Yin et al, 2018). Thus, providing enough hydraulic residence time.…”
Section:  Biological Methodsmentioning
confidence: 99%
“…Highly conductive leachate indicates a high concentration of dissolved solids which would provide adsorptive sites for biofilm inoculated for pollutants degradation. Low BOD/COD ratio and slightly high pH indicates that landfill leachate is in a stabilized state with minimal biodegradability of the organic components present (Ranjan et al, 2016). The COD/TOC ratio of the leachate < 2, is an indication of non-biodegradability .…”
Section: Leachate Formationmentioning
confidence: 99%
“…Similarly, Ghanizadeh and Sarrafpour [67] found that an increase in pH from 5.7 to 9.0 resulted in a significant decrease in the SVI from 96 to 44 mL/g. A considerable drop in the SVI from 90 and 80 mL/g to 30 and 20 mL/g was also observed with an increase in the concentration of leachate from a municipal solid waste dumpsite in wastewater from 2.5 to 15% and 40% in India and Poland, respectively [16,68]. An SVI below 70 mL/g may result in the turbid effluent associated with the dispersed growth of microorganisms and the formation of small pin flocs [69].…”
Section: Discussionmentioning
confidence: 99%
“…Spagnia and Marsili-Libelli [44] reported that low COD removal (about 20-30%) was obtained in SBR due to the low biodegradability in the LFL. Also, Ranjan [45] reported that COD removal was about 60-70%, but the NH4 + removal efficiency of more than 93% was obtained in SBR during LFL treatment.…”
Section: The Performance Of Aerobic Sequencing Batch Reactormentioning
confidence: 99%